Contribution of upper-body strength, body composition, and maximal oxygen uptake to predict double poling power and overall performance in female cross-country skiers - Østerås, S.; Welde, B.; Danielsen, J.; van den Tillaar, R.; Ettema, G.; Sandbakk, O. (The Journal of Strength and Conditioning Research, 2016)
Maximal oxygen uptake (VO2max) is regarded as the most performance-differentiating physiological measure in cross-country (XC) skiing. In addition, upper-body strength and lean mass have been associated with double poling (DP) power in XC skiers. In this study, we tested upper-body maximal strength, lean mass, and VO2max's contributions to predict DP power production of different durations and the overall XC skiing performance level of elite female XC skiers. Thirteen skiers (VO2max: 64.9 ± 4.2 ml/kg/min) performed one 30-second and one 3-minute DP performance test using a ski ergometer. The International Ski Federation's (FIS) ranking points determined their overall XC skiing performance. The skiers performed three 1-repetition maximal strength tests in poling-specific exercises that isolated the elbow extension, shoulder extension, and trunk flexion movements. Body composition was determined by a DXA scan, and VO2max was tested in an incremental running test. Multiple regressions were used to predict power production in the 30-second and 3-minute tests and FIS points. The 2 best predictions of 30-second DP power were lean upper-body mass and maximal upper-body strength (with the 3 strength tests normalized and pooled together as one variable) (R2 = 0.84 and 0.81, p < 0.001). Along with VO2max, the same 2 variables were the best predictions of both 3-minute DP power (R2 = 0.60 and 0.44, p = 0.05) and overall XC skiing performance (R2 = 0.43 and 0.40, p = 0.05). Although the importance of upper-body strength and lean mass to predict DP power production and the overall XC skiing performance declines with the performance duration in female XC skiers, the importance of VO2max shows an opposite relationship.